Analisis Implementasi Manajemen Perubahan dalam Pengelolaan Administrasi Pemerintahan di Kelurahan Ilir Gunungsitoli (Lembaga Pengembangan Kinerja Dosen, 2025)
Change management plays a crucial role in improving the effectiveness of government administration at the urban village level. In Ilir Gunungsitoli Urban Village, various challenges such as low human resource readiness, limited technological infrastructure, and resistance to change serve as obstacles to implementing digital-based administration. Additionally, a conventional bureaucratic culture hinders adaptation to new policies and technologies. Therefore, the strategic implementation of change management is necessary to enhance the competence of officials, strengthen supporting facilities, and foster a more adaptive work culture to improve the quality of public services. The objectives of this study are to examine the implementation of change management in the administration of government in Ilir Gunungsitoli Urban Village, to identify the challenges faced in implementing change management, and to determine strategies that can be applied to enhance the effectiveness of change management in government administration in Ilir Gunungsitoli Urban Village. This study uses a qualitative descriptive method. The research reveals that the changes in Ilir Gunungsitoli Urban Village include adjustments in organizational structure, initial implementation of digital technology, and changes in individual behavior. The organizational structure has become more adaptive, with clearer task distribution. The implementation of technology is still limited but has begun to aid service efficiency. Employees show a positive attitude toward change and are beginning to adapt to the new work system. The main challenges faced include limited infrastructure, low digital literacy, and human resource readiness. Overall, the changes made show progress but still require strengthening in employee capacity, supporting facilities, and internal synergy..